1999
DOI: 10.1046/j.1460-9568.1999.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Observation and execution of movement: similarities demonstrated by quantified electroencephalography

Abstract: Quantified electroencephalography (qEEG) was used to compare cerebral electrical variations while human subjects (10 males and 10 females) were observing and executing finger movements and while they were resting. Video recording enabled elimination of subjects performing involuntary movements. EEGs were recorded from 14 sites in seven frequency bands: theta 1, theta 2, alpha 1, alpha, beta 1, beta 2 and beta 3. Analyses were performed on logarithmically transformed absolute spectral power values. Both observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
264
3
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(298 citation statements)
references
References 20 publications
25
264
3
6
Order By: Relevance
“…Consistent with previous studies of neural oscillations during joint attention (Lachat et al, 2012), coordination (Tognoli et al, 2007, Dumas et al, 2012, Naeem et al, 2012a, and observation (Cochin et al, 1999, Caetano et al, 2007, 10 Hz suppression was found over left-central electrodes when interacting with another person versus a nonresponsive computer, with additional frontal components. While mu-rhythm suppression is well known to occur over the bilateral sensorimotor cortex (but stronger over the contralateral cortex) when engaging in motor activity in contrast to rest (Gastaut, 1952, Gastaut and Bert, 1954, Pfurtscheller and Lopes da Silva, 1999, it has also been found during action observation (Hari et al, 1998, Cochin et al, 1999, Caetano et al, 2007, and is hence thought to be part of a common coding mechanism of perception and action (Hari, 2006, de Lange et al, 2008.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies of neural oscillations during joint attention (Lachat et al, 2012), coordination (Tognoli et al, 2007, Dumas et al, 2012, Naeem et al, 2012a, and observation (Cochin et al, 1999, Caetano et al, 2007, 10 Hz suppression was found over left-central electrodes when interacting with another person versus a nonresponsive computer, with additional frontal components. While mu-rhythm suppression is well known to occur over the bilateral sensorimotor cortex (but stronger over the contralateral cortex) when engaging in motor activity in contrast to rest (Gastaut, 1952, Gastaut and Bert, 1954, Pfurtscheller and Lopes da Silva, 1999, it has also been found during action observation (Hari et al, 1998, Cochin et al, 1999, Caetano et al, 2007, and is hence thought to be part of a common coding mechanism of perception and action (Hari, 2006, de Lange et al, 2008.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, previous dual-EEG studies have consistently identified amplitude-modulation of oscillations around 10 Hz (alpha-band) over centro-parietal electrodes during joint attention and social coordination (Tognoli et al, 2007, Dumas et al, 2012, Lachat et al, 2012, which has also been reported in non-interactive experiments, during execution and observation of motor tasks (Cochin et al, 1999, Caetano et al, 2007) -corresponding to modulation in the rolandic mu rhythm (Gastaut, 1952). Interpersonally, two-brain studies have primarily focused on quantifying functional similarities or temporal synchronization between brains (Hasson et al, 2012) during interaction, showing evidence of inter-brain coupling when people engage in behaviourally coupled interactions (Dumas et al, 2010).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Sensorimotor tasks (Pineda, 2005), motor action execution, inhibition, and observation (Gastaut, 1952;Howe and Sterman, 1972;Niedermeyer and Lopes da Silva, 1993) are reflected in such mu oscillations. Additionally, both intracranial electrophysiology (Gastaut and Bert, 1954;Mukamel et al, 2010;Tremblay et al, 2004) and surface EEG (Cochin et al, 1999(Cochin et al, , 1998 consistently show comparable mu rhythm suppression during both the execution and the observation of different movements. Mu oscillations have also been investigated with respect to motor imagery (review in Neuper et al, 2006) and have been linked to mu suppression in parietal cortex, premotor, and primary sensorimotor areas (Pfurtscheller and Neuper, 1997;Pfurtscheller et al, 1997a).…”
Section: Introductionmentioning
confidence: 95%
“…In fact, this rhythm does not seem to reflect a unitary phenomenon (Pfurtscheller et al., 65 1996;Pineda, 2005;Stancak and Pfurtscheller, 1995), but rather a combination of different 66 processes, potentially involved in the transformation of ''seeing'' into ''doing''. Moreover, a 67 complete overview of the spectro--temporal dynamics within the AON is missing, since many 68 studies in the literature considered only the alpha component (Kilner et al, 2006; Marshall et al., 69 2009;Pineda et al, 2000;Streltsova et al, 2010), or limited their 70 attention to the amplitude modulation of the oscillatory activity (Cochin et al, 1999; Hari et al., 71 1998; Kilner et al., 2009;Koelewijn et al, 2008; Orgs et 72 al., 2008), whereas studies on the temporal dynamics of brain activity during OBS and EXE focused 73 on the sensorimotor cortex only (Babiloni et al, 2002;Caetano et al, 2007). 74…”
mentioning
confidence: 99%